A two-step optimization and statistical analysis of COD reduction from biotreated POME using empty fruit bunch-based activated carbon produced from pyrolysis - Amosa, Mutiu K.; Jami, Mohammed Saedi; Al-Khatib, Ma'an Fahmi Rashid; Jimat, Dzun Noraini; Muyibi, Suleyman Aremu (Springer Netherlands, 2015)
In this investigation, the potential of powdered activated carbon (PAC) derived from empty fruit bunch (EFB) precursor through pyrolysis method for chemical oxygen demand (COD) adsorption from biotreated palm oil mill effluent (POME) was extensively studied. The PAC was prepared and characterized using scanning electron microscope (SEM), Fourier transform infrared (FTIR) spectroscopy and Brunauer–Emmett–Teller. The SEM microphotographs showed opened micropores existing in the PAC structure with a surface area of 886.2 m 2 /g. The FTIR spectra revealed the three major peaks exhibited by the surface of the activated carbon at exactly wavenumbers of 1737.61, 1365.10 and 1216.91 cm -1 . This suggests the presence of some functional groups which can potentially enhance positive interactions between the adsorbent and the adsorbate.Design-Expert software (version 7.0.0) was employed for the statistical experimental design of a twostep optimization: factorial and response surface methodology. Maximum COD reduction of 84 % (227 ppm residual) was achieved from an initial concentration of 1387 ppm. This study being the first optimization process with the utility of EFB-based PAC in the treatment of the high-strength multicomponent biotreated POME; hence, the results could serve as requisite data for upscaling and/or future investigations in the utility of the precursor as a viable adsorbent.